Green Vehicle Routing Problem: Past, Present and Future - Somsai, Thanatporn; Pongcharoen, Pupong (Naresuan University Engineering Journal, 2020)
Green vehicle routing problem (GVRP) is a branch of traditional vehicle routing problems, which usually focus on the economic impact. Due to the environmental situation, the GVRP additionally plays more attention on both economic impacts and environmental issues. This review paper presents a literature survey on the topic of the GVRP by searching research articles indexed by three well-known international academic databases (including Scopus, ISI Web of Science and IEEE Xplore): After screening the duplications of the articles indexed by those three databases, only 171 articles were adopted and summarised into tables for classification into 3 characteristics: Green-VRP, Pollution Routing and VRP in Reverse Logistics. The result of literature review has found the future research direction for this problem should focus on the vehicle types, mode of transportation and other perspective of this research area is described in the future research direction section.